Cover. Issue 7 (12th July 2019) - Ma, Jing; Lin, Ken; Jiang, Hong‐chao; Yang, Yanli; Zhang, Yu; Yang, Guilian; Sun, Hao; Ming, Cheng; Bi, Xianyun; Zhang, Tiesong; Ruan, Biao
Abstract : The cover image based on Original Article A novel mutation of the PAX3 gene in a Chinese family with Waardenburg syndrome type I by Jing Ma et al., DOI:10.1002/mgg3.798 .